The effect of five Taraxacum species on in vitro and in vivo antioxidant and antiproliferative activity. Issue 8 (5th August 2015) - Mingarro, D. Muñoz; Plaza, A.; Galán, A.; Vicente, J. A.; Martínez, M. P.; Acero, N.
<x xml:space="preserve">Abstract</x> Differences between antioxidant and cytotoxic activities have been found among five Taraxacum species.